"In‐House" Data on the Outside—A Mobile Health Approach. Issue 4 (7th March 2020) - Huang, Qinlei; Crumley, Tami; Walters, Christina; Cluckers, Liesbeth; Heirman, Ingeborg; Railkar, Radha; Bhatia, Gaurav; Cantor, Matthew; Benko, Christopher; Izmailova, Elena S.; Rottey, Sylvie; Stoch, S. Aubrey
Abstract : Mobile health (mHealth) technologies have the potential to capture dense patient data on the background of real‐life behavior. Merck & Co., Inc. (Kenilworth, NJ), in collaboration with Koneksa Health, conducted a phase I clinical trial to validate cardiovascular mHealth technologies for concordance with traditional approaches and to establish sensitivity to detect effects of pharmacological intervention. This two‐part study enrolled 18 healthy male subjects. Part I, a 5‐day study, compared mHealth measures of heart rate (HR) and blood pressure (BP) to those from traditional methods. Hypotheses of similarity, in the clinic and at home, were tested individually for HR, systolic BP, and diastolic BP, at a 2‐sided 0.05 alpha level, with a prespecified criterion for similarity being the percentage differences between the 2 measurements within 15%. Part II, a 7‐day, 3‐period randomized balanced crossover study, evaluated the mHealth technology's ability to detect effects of bisoprolol and salbutamol. Hypotheses that the changes from baseline in HR were greater in the bisoprolol (reduction in HR) and salbutamol (increase in HR) groups compared with no treatment were tested, at a 1‐sided 0.05 alpha level. Linear mixed‐effects models, Pearson's correlation coefficients, summary statistics, and exploratory plots were applied to analyze the data. The mHealth measures of HR and BP were demonstrated to be similar to those from traditional methods, and sensitive to changes in cardiovascular parameters induced by bisoprolol and salbutamol.